THU0626 Cost-effectiveness of early treatment of acpa positive rheumatoid arthritis patients with abatacept. (15th June 2017) - Neubauer, AS; Minartz, C; Herrmann, KH; Postema, R; Baerwald, C
Abstract : Background: Studies have reported that the presence of elevated anti-citrullinated protein antibodies (ACPA)/RF levels, together with joint erosions, is associated with higher disease burden in terms of disability, and mortality in rheumatoid arthritis (RA). Abatacept has been shown to be effective in this patient population with favorable comparative data against adalimumab.(1) However, few studies have investigated the cost effectiveness of abatacept in this population to similar treatments such as TNFs. Objectives: The objective of the study was to compare the cost-effectiveness of abatacept to adalimumab as a first bDMARD in ACPA positive RA patients who failed treatment with methotrexate (MTX) in Germany. Methods: A decision tree model was used to estimate the cost-effectiveness, from a payer's perspective, of different treatment sequences in RA over a two year time frame. The effectiveness criteria were defined as achieving the treatment target measured by the Disease Activity Score 28 (DAS28 (CRP)<2.6; "remission"). A treatment switch to a different biologic as 2nd line and 3rd line bDMARD was allowed -in case of not achieving remission with therapy- every 6 months over a two year time period. Effectiveness data was based on randomized controlled trials (RCT) identified by an updated previous systematic literature search by the Institute for Quality and Efficiency in Health Care (IQWiG). Costs of medication and other direct medical costs were taken from a recent publication (2) and included in the analysis. Cost-effectiveness of RA treatment was investigated in ACPA positive patients in this study and presented as overall costs per day in remission. To manage uncertainty in the model, a fully probabilistic approach was used with 10, 000 runs. Results: For ACPA positive patients, treatment strategies including early treatment with abatacept had lower total costs per clinical outcome compared to later use. Figure 1 summarizes the costs per day in remission for the treatment sequences investigated: treatment sequences starting with abatacept resulted in lower costs for reaching remission (mean 330 €/day, range 328 €-333 €/day) compared to sequences starting with adalimumab (mean 384 €/day, range 378 €-390 €/day). Choice of the second or third biologic in the treatment sequences appears to have little impact on the costs per outcome. Conclusions: The results of this analysis suggest that in ACPA positive RA patients treatment with abatacept appears to be more cost-effective compared to treatment with adalimumab as a first bDMARD. References: Sokolove J, Schiff M, Fleischmann R, et al. Annals of the rheumatic diseases. 2016 Apr;75(4):709–14. Beresniak A, Baerwald C, Zeidler H et al. Clin Exp Rheumatol. 2013 May-Jun;31(3):400–8. Disclosure of Interest: A. Neubauer Grant/research support from: BMS, Intercept, Roche, Santen, C. Minartz Grant/research support from: BMS, Intercept, Roche, K. Herrmann Employee of: BMS, R. Postema Employee of: BMS, C. Baerwald Grant/research support from: Abbvie, Biogen, BMS, Chugai, Hexal, Medac, Pfizer, Roche, Sanofi Aventis, UCB